A Bibliographic Review of Concrete Obtained by Alkaline Activation and The Specific Case of The Municipal Solid Waste Incineration Slag - Ventura, Sebastião; Maia, Lino (Journal of Engineering and Applied Sciences Technology, 2025)
The present bibliographic review work focuses on the approach and study of historical processes of slag resulting from the incineration of municipal solid waste, namely: An introduction to the history of Roman civilization and its building habits in the region of Pozzuoli, its engineering and architecture; Alkaliactivated ligands, their Zeolitic compositions, geopolymers, chemical reactions and their crystalline phases, amorphous materials and the composition of aluminosilicates; Chemical and structural characterization of alkaline-activated materials and elements; Hybrid cements considered binders containing a percentage of OPC and another percentage of an aluminosilicate precursor and activated alcaline; Origin and treatment of municipal solid waste as well as incineration processes; Hybrid cements containing municipal solid waste incineration slag; An approach to the alkali activation of ligands with slag from municipal solid waste incineration. Finally, a conclusive top-down analysis of these issues.